2019
DOI: 10.1001/jamanetworkopen.2019.8265
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Aerobic Fitness and Maximal Muscular Strength With Metabolites in Young Men

Abstract: IMPORTANCE High physical fitness is associated with a reduction in risk of cardiovascular diseases and death, but the underlying mechanisms are insufficiently understood. OBJECTIVE To determine how aerobic fitness and muscular strength are associated with serum metabolome measures. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study included Finnish men receiving military refresher training from May 5, 2015, to November 28, 2015, representing partly overlapping groups of individuals with the lowest vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 68 publications
5
41
0
2
Order By: Relevance
“…To our knowledge, this is the first study to investigate prospective associations between aerobic fitness and a comprehensive lipoprotein profile in children. A recent cross-sectional study in adults examined associations of the serum metabolome between high and low aerobic fitness groups and showed a favourable pattern of associations with lipoprotein measures in those who were more fit [28]. In supplementary analyses, the authors demonstrated that although the associations of aerobic fitness with a number of individual measures were partly independent of age and body fat percentage, its inclusion as a variable in the regression models accounted for little additional variance compared to body fat percentage and age alone.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to investigate prospective associations between aerobic fitness and a comprehensive lipoprotein profile in children. A recent cross-sectional study in adults examined associations of the serum metabolome between high and low aerobic fitness groups and showed a favourable pattern of associations with lipoprotein measures in those who were more fit [28]. In supplementary analyses, the authors demonstrated that although the associations of aerobic fitness with a number of individual measures were partly independent of age and body fat percentage, its inclusion as a variable in the regression models accounted for little additional variance compared to body fat percentage and age alone.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption frequency was categorized as none, once a month or less, 2–4 times per month, 2–3 times per week, 4 or more times per week. BMI, physical activity, alcohol use and smoking have been shown to be related to both metabolite levels 26 , 35 37 and aggression 38 40 . Finally, self-rated general health was dichotomized to either poor health (poor + fair) or good health (good + very good).…”
Section: Methodsmentioning
confidence: 99%
“…Less clear is the degree to which aerobic fitness and muscular strength contribute to mediators of cardiovascular health. In a cross-sectional study of 580 Finnish men by Kujala et al, 8 that assessed the association of push-up capacity with cardiovascular outcomes. Compared with firefighters completing fewer than 10 push-ups, those able to complete more than 40 push-ups had a lower risk of cardiovascular events.…”
Section: How Does Fitness Contribute To Cardiovascular Health? Is Aermentioning
confidence: 99%
“…Activities to maintain muscular strength are important to maintain physical function, and prior studies of individuals with diabetes18 suggest resistance training in combination with aerobic training leads to greater improvements in blood glucose levels than either training alone. However, the study by Kujala et al8 suggests that aerobic fitness is the stronger contributor to markers of cardiovascular health for most individuals.Although the previously discussed studies used detailed assessments of activity and fitness, in clinical care it doesn't always need to be complicated. Prior studies have demonstrated associations of simple measures of fitness (eg, grip strength 19 or 6-minute walk test 20 ) with patient outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation